Corporate Criminal Liability for Alleged Criminal Acts of Employing Medical and Health Workers Without Permission in Hospitals - Beni Satria (Yayasan Multidimensi Kreatif, 2024)
Corporations as legal subjects not only carry out their activities in accordance with economic principles (seeking large profits) but also have an obligation to comply with legal regulations in the health sector used by the government to realize community welfare and social justice. The corporation as the maker, the management responsible for the criminal act can be committed by the association or business entity (corporation), but the responsibility for it is the burden of the management of the legal entity (corporation). Gradually, criminal responsibility shifts from the members of the board to those who order, or by the prohibition of doing so if they neglect to lead the corporation in practice. The purpose of the study: to understand the form of corporate responsibility as a legal entity of hospitals in employing medical personnel and health workers without practice licenses (permits) in hospitals. This study uses a descriptive analytical normative juridical approach with secondary data from literature studies through primary, secondary and tertiary legal materials related to corporate crimes, hospital legal entities, licensing of medical personnel and health workers in Indonesian criminal law. The data was analyzed using qualitative analysis. Conclusion: In the accountability system for hiring medical personnel and health workers without a practice license (permit), the corporation can become the perpetrator of the crime, but the responsible are the members of the management, as long as it is expressly stated in the regulation. Corporations as makers or those who give orders/orders to employ medical personnel and health workers to work without permission. Managers are appointed as responsible; What is seen as done by a corporation is what is done by the complementary tools of the corporation according to its authority based on its articles of association.